Ex vivo antiplasmodial activity of Quassia Borneensis Noot. (SIMAROUBACEAE) extracts against mice erythrocytes infected by Plasmodium Berghei NK 65 / Ahmad Rohi Ghazali, Julenah Ag Nuddin, Siti Nurfarhana Sabireen, Wan Marahaini Wan Razali and Shafariatul Akmar Ishak - Ghazali, Ahmad Rohi; Nuddin, Julenah Ag; Sabireen, Siti Nurfarhana; Wan Razali, Wan Marahaini (Faculty of Business Management, 2013)
This study is attempts to determine antimalarial activity of Q. borneensis extracts against the intraerythrocytic phase of P. berghei NK65. Parts of Q. borneensis was extracted by cold maceration and soxhlet in 10% aqueous methanol before partitioned with n-Hexane, and chloroform. The extratcs were subjected to colorimetric Plasmodium Lactate Dehydrogenase Assay (pLDH). The extract with most potential IC50 was later evaluated in synchronization test. It was found that hexane soxhlet extract of root, (Qb4), and chloroform soxhlet extract of bark, (Qb7) showed potential, at the values of IC50 0.039μg/ml and 0.001μg/ml, respectively. In the synchronization test, Qb7 extract was found to be active against all three stages of parasites in the intraerythrocytic phase, with the IC50 value for the early, late trophozoite and schizont at 1.964 μg/ml, 0.0009μg/ml and 0.007 μg/ml respectively. This study coulclude that Q. borneensis might possess biologically active quassinoids which could contribute to their antimalarial activities.